A challenging case of anemia, respiratory failure and seizures - Bova, Carlo; De Bartolo, Tommaso; De Stefano, Roberto; Ruvio, Martina (Acta Biomedica Atenei Parmensis, 2022)
Background. Hemorrhagic Hereditary Telangiectasia (HHT), or Rendu-Osler-Weber syndrome, is a rare genetic disorder characterized by mucocutaneous telangiectasias and visceral arteriovenous malformations. Aim and Methods.We describe the case of a 64-year old woman in which radiology was useful to interpret an apparently unexplained constellation of symptoms. Results. Brain MRI showing ischemic stroke, pulmonary angiography demonstrating arteriovenous malformations, and capsule endoscopy detecting telangiectasias in the jejunum, along with a clinical history of recurrent epistaxis, allowed us to diagnose HHT. Conclusions. HHT is rare and difficult to diagnose. Radiology can aid the clinical suspicion. www.actabiomedica.it